The Interpersonal Meaning Realized in The Lyrics of Christina Perri’s Album “Lovestrong” and The Contribution for Teaching a Modern English Grammar - Dias Andris Susanto; Setiyo Watik (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2017)
This study examines the interpersonal meaning realized in the lyrics of Christina Perri’s Album “Lovestrong” and the contribution for teaching of a modern English grammar. It will be easier and more interesting to analyze the interpersonal meaning through the literary works that we hear everyday such as song lyrics.The objectives of this study are to describe the interpersonal meaning realized in the lyrics of Christina Perri’s Album “Love strong”, to know the most dominant Mood Types and Speech Roles, to describe the Modality realized in those lyrics and to describe the contribution of interpersonal meaning in the lyrics of Christina Perri’s Album “Love strong”. The design of the research was descriptive qualitative. The main sources of data in this research were the lyrics of Christina Perri’s Album “Love strong”. There were five song lyrics that the writers analyzed in this study. The analysis of the data used the following steps: those followings, listened to the songs, found the printed lyrics of the songs, analyzed the clauses based on the Mood-Residue elements and found the Modality through Modal Finite and Mood Adjunct. Next step, the writer classified the clause to get the most dominant of Mood Types and Speech Roles. The last, the writers drew the conclusion of this study. The results of data analysis shows that the interpersonal meaning in the lyrics of Christina Perri’s Album “Love strong” realized in the wordings of the clause if analyzed based on the elements of interpersonal meaning, the most dominant Mood Types is Declarative, the most dominant Speech Roles is Giving Information, the Modality realized through the use of modal finite and mood adjunct, and the contribution of interpersonal meaning in the lyrics of Christina Perri’s Album “Love strong” for teaching of a modern English grammar is to help the students easier and more interesting to analyze the interpersonal meaning through the lyrics of their favorite song or favorite singer. The conclusions of this study are; the realization of the interpersonal meaning in the song lyrics, we should read them thoroughly while analyzing based on the interpersonal meaning elements. Based on the Mood Types and Speech Roles analysis, the song writer or singer wants to declare something and give information to the readers or listener through these songs. Keywords: interpersonal meaning, song lyrics, mood types, modality, modern English grammar